Unlimited Buy-backs: What are they good for? - M, Holub (Institutional Knowledge at Singapore Management University, 2011)
Our article investigates the use of unlimited buy-backs, which have been permitted in Australia since September 1999, using data over the period 2000–2009. We discuss a number of inconsistencies between the Corporations Act, ASIC regulations and ASX requirements and the confusion surrounding the terms continuous and indefinite duration. In particular, we note that allowing for buy-backs of unlimited duration appears to be at odds with the use of a 12 month time period in the operative 10/12 rule in the Corporations Act. We discover that incongruent information has often been reported by companies using unlimited buy-backs and that companies do not always conform with ASX requirements such as the need to disclose active buy-backs in corporate annual reports. We provide examples of corporate practices to illustrate our points. We find that most unlimited buy-backs are completed within a 12 month period. Further, we find little difference in the structural characteristics of unlimited and defined period buy-backs. Our results lead us to question the reasons advanced for unlimited period buy-backs. We recommend that the practice of allowing unlimited buy-backs be discontinued and that a 12 month maximum time period be enforced for all buy-backs. This will remove the uncertainty inherent in buy-backs having unlimited duration and improve the information content of buy-backs in general.